y = (x+a)(x+b) = x^2 + x (a+b) +ab. -a, -b are the two points where the curve intersects x-axis

From Stmt 1, a + b = -1

a = -7, b = 6 or a = 6, b = -7 Not Sufficient

From Stmt 2, substituting point (0, -6) in y = x^2 + x(a+b) + ab => -6 = ab

a = -6, b = 1 or a = 1, b = -6 Not Sufficient

Taking Stmt 1 and Stmt 2

ab = -6 and a+b = -1

-b^2 -b + 6 = 0 => (b + 3)(b - 2) = 0 => b = -3 or 2 => a = 2, -3. Both these values lead to the same two points - 3 and -2 Therefore answer is C.

Hope this helps

_________________

KUDOS is a way to say Thank You